1999
DOI: 10.1080/00103629909370312
|View full text |Cite
|
Sign up to set email alerts
|

Dewatered anaerobically‐stabilized primary sewage sludge composting: Metal leachability and uptake by natural Clinoptilolite

Abstract: Environmental problems associated with sewage sludge disposal have prompted strict legislative actions over the past years. At the same time, the upgrading and expansion of wastewater treatment plants have greatly increased the volume of sludge generated. The major limitation of land application of sewage sludge compost is the potential high heavy metal content in relation to the metal content of the original sludge. Composting of sewage sludge with natural zeolite (Clinoptilolite) can enhance its quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 11 publications
(13 reference statements)
0
15
0
7
Order By: Relevance
“…For ratios higher than 5, characteristic of fulvic acid are shown. [24,26,27] In a separate set of experiment aimed to distinguish humic acid from fulvic acid, the E4/E6 values for the sewage sludge, the extracted EPS, and the microwave treated samples were 2.3, 2.3 and 2.2, respectively. Therefore, humic substances reported in the Table 1 were most likely to be humic acids.…”
Section: Extraction Of Epsmentioning
confidence: 99%
“…For ratios higher than 5, characteristic of fulvic acid are shown. [24,26,27] In a separate set of experiment aimed to distinguish humic acid from fulvic acid, the E4/E6 values for the sewage sludge, the extracted EPS, and the microwave treated samples were 2.3, 2.3 and 2.2, respectively. Therefore, humic substances reported in the Table 1 were most likely to be humic acids.…”
Section: Extraction Of Epsmentioning
confidence: 99%
“…Clinoptilolite is the most abundant source of natural zeolite and has the chemical formula Na (Galli et al, 1983). Earlier studies have shown that clinoptilolite, and certain other natural zeolites are effective in removing ammonia from wastewater (Emadi et al, 2001;Zorpas et al, 1999). However, there are few studies on the effects of natural zeolites on ammonia reduction during the thermophilic stage of food waste composting.…”
Section: Introductionmentioning
confidence: 97%
“…It has also found application in removal and purification of cesium and strontium radioisotopes. Natural zeolites nowadays are mostly used in catalysis, in air enrichment, as filters in paper and rubber industry, in soil benefication, as animal feed supplements, and in water and wastewater treatment [13].…”
Section: Introductionmentioning
confidence: 99%